Minimally of polyphenol oxidase activity and controlling of rotting and browning of longan fruits cv. DAW by SO2 treatment under cold storage conditions - Wilasinee Chitbanchong (2018)
The effects of sulphur dioxide, in combination with, storage temperatures on postharvest decay, pericarp browning and physiological ultrastructure changed of the Longan fruit cv. daw were studied. The treatment of fresh the Longan fruit with SO2 fumigation combined with the suitable storage condition improved the overall the Longan fruit quality, especially on inner and outer peel tissue and aril color than no SO2 treatment, while no SO2 treatment showed the dark color of inner and outer peel of the Longan fruit was appeared, this was correlated with the increasing of polyphenol oxidase (PPO) activity. Moreover, the main factor affected Longan fruits quality was storage duration, the increasing of weight loss, pH value of both peel and aril, PPO activity, especially on the changing of dark-red color of peel was observed after long term of storage. However, the sulphite residues could detect immediately after SO2 treatment in all part of the Longan fruit, especially on peel tissue, but the residues was significantly decreased along the storage durations. On the other hand, Scanning Electron Microscope (SEM) evaluation found that the surface cracking was also impair the physiological function of the cuticle and increasing water permeability, which may cause water soaking at the inner side of the peel. The injured cell would accelerate the oxidation of phenolic substances and the oxidative products resulted in dark color of inner and outer peel. Therefore, the combination sulphur dioxide fumigation with controlling the optimum of storage temperature could control of postharvest decay and browning. © 2009 Academic Joumals Inc.